Refactoring the Web Interface - Howell, Jon; Parno, Bryan; Douceur, John (JD) (SOSP 2011 Poster Session, 2011)
The web browser, which originated as a simple viewer for displaying static webpages, has evolved into an operating system for executing web applications. The quantity, diversity, and capability of web applications have grown dramatically, such that many modern web applications have begun to rival the breadth and functionality of desktop applications. What has fueled this trend? Why do users ﬁnd a browser to be a better application platform than a traditional operating system?